2014
DOI: 10.4161/rna.28141
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of themiR199-214cluster and vertebrate skeletal development

Abstract: The miR199 and miR214 genes occupy an intronic cluster located on the opposite strand of the Dynamin3 gene. These miRNAs play major roles in a broad variety of developmental processes and diseases, including skeletal development and several types of cancer. In the work reported here, we first deciphered the origin of the miR199 and miR214 families by following evolution of miR paralogs and their host Dynamin paralogs. We then examined the expression patterns of miR199 and miR214 in developing zebrafish embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 92 publications
(122 reference statements)
1
52
0
Order By: Relevance
“…miR-199a2 is located within the DNM3os transcription unit. This long noncoding RNA transcript is responsible for synthesis of the miRNA cluster containing miR-199a2 and miR-214 and is involved in skeletal development (42,43). Accordingly it was necessary to determine whether PlGF regulated synthesis of the long DNM3os transcript, as previously observed, or instead led to independent transcription of premir-199a2.…”
Section: Discussionmentioning
confidence: 93%
“…miR-199a2 is located within the DNM3os transcription unit. This long noncoding RNA transcript is responsible for synthesis of the miRNA cluster containing miR-199a2 and miR-214 and is involved in skeletal development (42,43). Accordingly it was necessary to determine whether PlGF regulated synthesis of the long DNM3os transcript, as previously observed, or instead led to independent transcription of premir-199a2.…”
Section: Discussionmentioning
confidence: 93%
“…37 The expression study showed predominant expression patterns for miR-199-214 cluster in tissues surrounding developing craniofacial skeletal elements and indicated a conserved role of miR-199 and miR-214 in vertebrate skeletogenesis. 38 miR-199-214 is essential to skeletogenesis because miR-199-214 cluster knockout mice display skeletal abnormalities. 20 In our study, we found that miR-214 plays an important role in osteoclastogenesis and affects osteoclast activity through regulating the expression of osteoclast functional genes.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish smallRNA-seq dataset clearly contained three pairs of mirror-mirs (Table 1), which are defined as a pair of mir genes originating from overlapping genomic regions but on opposite strands (Tyler et al, 2008; Scott et al, 2012). For example, the expression of mir3120 , mirror-mir of mir214 , has been described in mammals but in no other species (Scott et al, 2012; Desvignes et al, 2014). Here we show that miR3120 , a mature fragment originating from the mirror-mir of mir214 , is expressed in adult zebrafish.…”
Section: Resultsmentioning
confidence: 99%